Dentoalveolar effects of skeletally anchored extrusion arch in anterior open bite patients: A prospective clinical trial - Noheir Samir ELSHAL; Mohammad Hasan MOHAMMAD; Marwa Ali TAWFIK; Maher Abd El-Salam FOUDA (Dental Press Editora, 2024)
ABSTRACT Objective: The purpose of this prospective clinical trial was to explore the dental and soft tissue changes accompanying the use of skeletally anchored nickel-titanium (NiTi) extrusion arch in the correction of anterior open bite (AOB). Material and Methods: Twenty female patients with a mean age of 16.5 ± 1.5 years and a mean dentoalveolar AOB of 2.38±0.7 mm participated in this study. All patients were treated with an maxillary 0.017×0.025-in NiTi extrusion arch, with the aid of miniscrews inserted between the maxillary second premolars and first molars bilaterally, to act as indirect anchorage. Three-dimensional digital models and lateral cephalometric radiographs were taken just before the insertion of the extrusion arch (T0) and after 10 months (T1). Paired-sample t-tests were used in analyzing the data, to evaluate the changes after treatment (T1-T0). A significance level of p < 0.05 was used. Results: AOB was successfully closed in all patients, with a 4.35 ± 0.61 mm increase in the overbite. Maxillary incisors significantly extruded (2.52 ± 1.02 mm) and significantly reclined (5.78 ± 0.77°), with a resultant decrease in the overjet of 1.58 ± 0.5mm. A significant intrusion of maxillary first molars with no change in their inclination was observed. The upper lip showed a significant retraction tendency to the E-plane, and a significant increase in the nasolabial angle was observed. Conclusion: The skeletally anchored NiTi extrusion arch was an effective technique in treating AOB, with no adverse effects on the molars.